Probing the compositional and rheological properties of gastropod locomotive mucus - Barajas-Ledesma, Edgar; Holland, Chris (Frontiers in Soft Matter, 2023)
Gastropods, such as snails and slugs, can excrete mucus to aid in movement and adhesion. However, to date, there are very few studies looking at the physical relationship between mucus composition and function. Here, we explore the role of mucus polymers (specifically its proteins) and their influence on the material properties of locomotive mucus. Using a range of spectroscopic, thermal, and rheological analytical tools, we characterised locomotive mucus from 6 gastropod species across 4 families. We report that all mucus tested consisted of 97-99% water with the remaining 1-3% solids content contained a range of proteins (41-377 kDa, of which 18 are previously undocumented) which we propose contribute to its weak gel behaviour (1.58-36.33 Pa.s at 1 rad/sec). Our results indicate mucus properties are also grouped at the family level, suggesting niche-specific adaptation occurs in these materials. We expect our study to offer a broader approach of how a correlation between properties is crucial for the understanding of the stability and functionality of snail mucus.